Canine Interferon-Inducible Transmembrane Protein Is a Host Restriction Factor That Potently Inhibits Replication of Emerging Canine Influenza Virus - Lu, Gang; Ou, Jiajun; Cai, Siqi; Lai, Zhiying; Zhong, Lintao; Yin, Xin; Li, Shoujun (Frontiers in Immunology, 2021)
Canine influenza virus (CIV) is an emerging virus that is associated with major hidden hazards to the canine population and public health. Until now, how canine uses its innate immunity to restrict CIV replication is seldomly investigated. Recently, studies on interferon-inducible transmembrane (IFITM) of several major hosts of influenza virus (human, chicken, duck, pig) indicated it can potently restrict the viral replication. Here, the gene locus of five previously annotated canine IFITM (caIFITM) genes was determined on chromosome 18 using multiple bioinformatics strategies, provisionally designated as caIFITM1, -2a, -2b, -3, -5. An analysis on protein sequences between caIFITM and its homologues indicated they shared the same conserved amino acids important for the antiviral activity. Expression profile analysis showed that caIFITM was constitutively expressed in tissues and MDCK cell line. After treated with interferon or infected with influenza virus, the expression level of caIFITM increased with different degrees in vitro. Animal challenge study demonstrated CIV infection resulted in up-regulation of caIFITM in Beagle dogs. caIFITMs had a similar subcellular localization to their human homologues. caIFITM1 was present at cell surface and caIFITM3 was present perinuclearly and colocalizated with LAMP1-containing compartments. Finally, we generated A549 cell lines stably expressing caIFITM and challenged them with influenza virus. The result demonstrated caIFITM1, -2a, -2b, -3 had a potent antiviral activity against influenza virus. Our study will help better understand the evolutional pattern of IFITM and its role in the host’s defense against virus infection.